Yoga Hatha untuk Mengurangi Fatigue pada Pasien Kanker Payudara - Martikasari, Msy.; Afiyanti, Yati; Widyatuti, Widyatuti (FORIKES, 2024)
Fatigue is one of the most common side effects experienced by breast cancer patients and has a significant impact on their quality of life. This review aims to evaluate the effectiveness of yoga in reducing fatigue levels in breast cancer patients. This study was conducted using a systematic review method, through a literature search in several databases including the Cochrane Library, PubMed, Sage, ScienceDirect and Taylor and Francis with the keywords: